Main obstacles in the business environment affecting firm growth: a comparative analysis between Chinese and Brazilian SMEs - Tricaud, Chloé Sandrine Hélène (2015)
Using World Bank Data, this research analyzes the similarities and differences in the main obstacles faced by Chinese and Brazilian micro, small and medium enterprises (MSME). We performed both country and cluster analyses in order to confront subjective and objective data, with the aim to be able to identify firms’ behaviors according to their own characteristics and their country environment.